(untitled) (Nexo Revista Científica, 2023)
This research is dedicated to investigating the structural performance of high-strength strengthened concrete beams in resisting shear forces when stirrups (ST)-carbon fiber (CF) and steel fiber (SF) materials are used as shear reinforcement. Shear reinforcement has been provided in either of the two forms. The first form consisted of steel fibers of two volume fractions: Vf=0.5% and Vf=1.0%. The second form consisted of ST of two configurations: Φ8mm@300mm and Φ8mm@200mm, which experimentally have equivalent shear effects to the SF of 0.5 and 1.0% fiber content, respectively. With both forms, a 45ᵒ inclined CF material has been externally applied. In addition to the reference beam of no form of shear reinforcement, a total of nine beams were tested for failure under the “four-point bending” test, and the results obtained were reported and discussed in terms of the maximum load capacity, failure mode, and deflection. The results obtained indicated the great contribution of CF in providing extra resistance to the applied shear forces regardless of whether a beam had been reinforced in terms of ST or SF. However, the contribution of CF is more pronounced (more than double) when the high-strength beams were reinforced utilizing SF as compared to the ST.